Philosophy And Technologi In The Digital Era - Humau, Yulinda Makdalena; Asadama, Mia; Lelo, Kaleb; Liufeto, Desi Alyani; Lasena, Yeni Felpina (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The advancement of digital technology has brought fundamental changes to various aspects of human life, ranging from ways of communication to how knowledge is produced and disseminated. A lecturer in the Philosophy of Science course addressed the technological revolution in the digital era. Students in the Early Childhood Christian Education program at IAKN Kupang utilized technology wisely through a seminar activity with the theme